Tic disorder in the pediatric population - Zorcec, T; Duma, F; Angelkova N (SHMSHM / AAMD, 2017)
Tics are defined as a recurrent, non-rhythmic series of movements, of a non-voluntary nature, in one or several muscle groups. Tics are sudden twitches, movements, or sounds that people do repeatedly. They can take place anywhere on the body and be very frequent. The lifetime prevalence of tic disorder is not known but estimates vary between 5% and 10% of the population, with estimations of 18% in child population. No definitive cause of tics has been discovered yet. Vulnerability to tic disorders seems to be genetic or to run within families, even though no single gene has been found. High rates of comorbid conditions are recognized in persons with tic disorders especially in patients with Tourette syndrome, like obsessive-compulsive disorder, attention-deficit/hyperactivity disorder and anxiety disorders. Currently, there is no one effective cure for tic disorders, but there are treatments that can help manage them. The therapeutic approach should be determent individually and conducted by multidisciplinary team.
Keywords: tic disorder; pediatric population